Design, Synthesis, and in vitro and in vivo Evaluations of (Z)‐3, 4, 5‐Trimethoxystyrylbenzenesulfonamides/sulfonates as Highly Potent Tubulin Polymerization Inhibitors. (13th April 2017) - Mahesh, Rasala; Nayak, Vadithe Lakshma; Babu, Korrapati Suresh; Riyaz, Syed; Shaik, Thokhir Basha; Kumar, Gajjela Bharth; Mallipeddi, Prema Latha; Reddy, Challa Ratna; Shekar, Kunta Chandra; Jose, Jedy; Nagesh, Narayana; Kamal, Ahmed
Abstract: Newer therapeutics can be developed in drug discovery by adopting the strategy of scaffold hopping of the privileged scaffolds from known bioactive compounds. This strategy has been widely employed in drug‐discovery processes. Structure‐based docking studies illustrate the basic underlying concepts and reveal that interactions of the sulfonamide group and hydrophobic interactions are crucial. On the basis of this strategy, over 60 synthetic analogues were synthesized and evaluated for their cytotoxicity against the NCI panel of 60 human cancer cell lines; the majority of these compounds exhibited promising cytotoxicity with GI50 values ranging between 18 and 50 nm . Among these compounds, ( Z )‐ N ‐[2, 3‐dimethoxy‐5‐(3, 4, 5‐trimethoxystyryl)phenyl]‐4‐methoxybenzenesulfonamide (7 a ) and ( Z )‐ N ‐[2‐hydroxy‐3‐methoxy‐6‐(3, 4, 5‐trimethoxystyryl)phenyl]‐4‐methoxybenzenesulfonamide (9 a ) were found to be potent. Similar results were obtained against three human cancer cell lines with IC50 values ranging between 0.04 and 3.0 μm . Studies aimed at elucidating the mechanism of action of these new analogues revealed that they inhibited the in vitro polymerization of tubulin and disorganized the assembly of microtubules in HeLa and MCF‐7cancer cells. Lead compounds7 a and9 a displayed notable in vivo antitumor activity in a HeLa tumor xenograft model. Our studies have resulted in the identification of a scaffold that can target tubulin polymerization, which should have significant potential toward the development of new antitumor drugs. Abstract : Inhibiting polymerization : ( Z )‐3, 4, 5‐Trimethoxystyrylbenzenesulfonamides/sulfonates were designed, synthesized, and evaluated for their cytotoxicity against the NCI panel of 60 human cancer cell lines. The majority of these compounds exhibit promising cytotoxicity, with GI50 values in the 18–50 nm range. We identified a scaffold that can target tubulin polymerization, and this scaffold should have potential for the development of new antitumor drugs.